Profil postural chez des sprinteurs et des sauteurs de haut niveau - Hammami, R.; Chaouachi, A.; Bouafif, N.; Ben Achour Lebibe, S.; Ben Salah, F.-Z. (Science & Sports, 2012)
Objective To study the hamstring injuries effects on static balance in elite Tunisian sprinters and jumpers. Methods A group of eight elite athletes including sprinters and jumpers with previous hamstring injuries were compared to a control group of non-injured athletes (n = 8). The postural assessment was made on a platform Neurocom® Balance Master and contained tests estimating the control of the static balance. Results Our investigation showed that except the eyes closed unstable surface condition (P < 0.04), there are no significant differences in the weight-bearing distribution between groups in postural stability. A significant difference in distribution between groups was observed (P < 0.001). Conclusion The completion of an unusual and unstable task modified the static balance of our athletes demonstrating the possible influence of a muscle weakness or a joint limitation. It is recommended to include postural assessment to asses balance deficits to guide treatment, training and to prevent the risk of muscle damage.